FORMATION OF FOREIGN LANGUAGE ACADEMIC WRITING COMPETENCE BASED ON ENQUIRY-BASED LEARNING - Ainur Madiyarbek (World Scientific Reports, 2023)
Academic writing in a foreign language is a complex task that requires not only knowledge of grammar and vocabulary but also an understanding of academic discourse, genre conventions. Enquiry-based learning is an approach that emphasizes students’ active participation in the learning process, including posing questions, investigating, and reflecting on their findings. In this article, we will discuss how enquiry-based learning can be used to develop foreign language academic writing competence. Enquiry-based learning involves students working in teams to solve real-world problems or answer questions with data they have collected themselves. Teachers serve more as tutors than instructors, where they explain and demonstrate lessons. The purpose of this article is to explore the development of foreign language academic writing competence through enquiry-based learning. The object of the article is the process of using enquiry-based learning in teaching.